Development characteristics and river blocking outburst analysis of Shadong landslide in the upper reaches of Jinsha River - Shunxiang ZHENG; Jun WANG; Yong YAN; Wen LIU; Heng ZHAO; Junxiang YANG; Xiongan FAN; Yi ZHANG; Meng WANG; Tianbin YU (Shuiwen dizhi gongcheng dizhi)
The Shadong landslide, located in the Jinsha suture belt, exhibits significant signs of deformation. It is a high risk of developing into a disaster chain of landslide, river blockage, and flood, posing a serious threat to major engineering construction, transportation facilities, and people's lives and property. In this study, multi-source remote sensing dynamic monitoring, engineering geological survey, and numerical simulation were used to analyze the deformation characteristics and explore the risk of river blocking outburst of the Shadong landslide. The results show that the Shadong landslide is a giant landslide with a volume of approximately 23045×104 m3. The landslide is currently in the stage of creep deformation, with continuous deformation from 2018 to 2023. The reactivation deformation area of the landslide is mainly concentrated at the front edge of the slope, and the deformation on the downstream side is stronger than that on the upstream side. The Shadong landslide slides along the bedrock cover interface, exhibiting a traction type progressive failure. Based on stability analysis, three potential instability modes have been established. Under natural conditions, the leading edge of the secondary landslide C3 is unstable, with the landslide event lasting around 35 seconds. The maximum speed of the landslide reaches 30 m/s. The height of the barrier dam is about 90 m, and the barrier lake capacity is about 1.62×108 m3, with a maximum flood flow of approximately 3535 m3/s and a flood peak height of approximately 14 m at the dam site of the Lava Power Station after the barrier dam failure. Under storm conditions, instability occurs in zone II-2, forming a 133-meter-high barrier dam with a lake capacity of approximately 4.10×108 m3. The maximum flood flow could reach 11315 m3/s, with a maximum flood peak height of approximately 31 m at the Lava Power Station. In the event of both storm and earthquake conditions, II-1 and II-2 zone are unstable at the same time, resulting in the height of the barrier dam of approximately 153 m, with a barrier lake capacity of approximately 5.66×108 m3. The maximum flood flow is approximately 19960 m3/s, with a maximum flood peak height of approximately 45m at the dam site of the Lava Power Station after the barrier dam failure. Given the high risk of river blockage and the catastrophic potential of the Shadong landslide, continuous monitoring through integrated sky, air, ground, and interior methods is recommended. Additionally, further study is needed to establish early warning thresholds and accurately manage the risk of major geological disasters.